Study of foetomaternal outcome of antepartum haemorrhage in pregnancy - Majumder, Siddhartha; Shah, Parul T.; Deliwala, Kruti J.; Patel, Rina V.; Madiya, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Any bleeding from the genital tract during pregnancy, after the period of viability until the delivery of the fetus (end of second stage), is defined as antepartum hemorrhage. The World Health Authority defines antepartum haemorrhage as bleeding after 28 weeks of pregnancy. At the country level, the two countries that accounted for one third of all global maternal deaths are India at 17% and Nigeria at 14% in 2013. Maternal health and newborn health care are closely linked. Almost 3 million newborn babies die every year and an additional 2.6 million babies are stillborn. With improvement in medical facilities, early diagnosis, availability of blood transfusion, good anesthesia, proper management of shock and other complication of pregnancy along with liberalization of caesarean section, the rate of maternal morbidity and mortality is gradually on the decline. Methods: This is a prospective study of 100 cases of APH admitted during the period of May 2014 to April 2015 at a tertiary care hospital. Patients in third trimester of pregnancy with APH have been included in this study. Results: In present study incidence of APH is 3.8% and of the 100 sample cases 66 cases were of placenta previa and 34 cases were of abruptio placenta. In the present study 64% were emergency cases. Incidence of APH was 60% in age group 21-30 years of which 70% cases were noted with parity of >2. Ultrasonography was very much helpful in diagnosing placenta previa (93.9%), while most cases (76.4%) of abruptio placenta were diagnosed clinically. At the time of admission 75% patients were anaemic and many required blood transfusion. The perinatal mortality rate of abruptio placenta is 44.1% and placenta previa is 12.1%. Perinatal loss is 22.5% for up to foetus weighing 2 kg, 18.7% for foetus weighing between 2.1-2.5 kg and 27.02% for those ≥2.6 kg. Conclusions: Educating pregnant mothers about the importance of antenatal care and easy accessibility to quality antenatal services would go a long way in bringing down the maternal and perinatal morbidity and mortality related with antepartum haemorrhage. The morbidity associated with placenta previa can be reduced by detecting the condition in the antenatal period by ultrasound, before it becomes symptomatic. Intensive family planning program and awareness of small family norm helps in decreasing cases ofAPH in relation with age and parity. Efforts should be made to reduce the rates of operative deliveries, because there is a greater likelihood of placenta previa in a scarred uterus. There is a lot of scope on further research in the field ofAPH for further reduction in foetal and maternal morbidity and mortality.